Evaluating Scientific Potential in Kazakhstan: A Regional Index Assessment Approach - O. S. Adilkhanov; O. S. Sabden; Sh. K. Turdalina; Sh. Zh. Tuebekova (Экономика: стратегия и практика, 2024)
The role of human resources in increasing competitiveness is enormous, including people with higher education, a certain status or academic degree, as well as knowledgeable human resources. The objective is to identify the scientific potential across Kazakhstan’s regions using the index assessment method and to analyze the differences between regions. Thus, the authors determine the scientific potential in the regions by the method of index assessment, using factors such as the proportion of people working in the field of science in the region and the amount of spending on science in that region. Conducting a regional analysis provides important information in the management of the state. According to this rating, the cities of Abay region (0.27), Almaty (0.58) and Astana (0.44) were in the lead, and Turkestan (0.02), Atyrau (0.02) and Ulytau (0.001) were in the last place.After all, since most of the scientific research organizations and universities are located in Astana and Almaty, the funds allocated from the Center for science and the number of people engaged in science are concentrated in these cities. This article also revealed the correlation of factors affecting the number of people involved in science in the country’s regions. As a result of the study, it was found that the number of people engaged in science in the regions is directly affected by the internal costs of research work in the regions. At the end of the article, recommendations were given on increasing scientific and high intellectual potential. These recommendations can be used by persons and organizations interested in the development of Science in the regions and applied to the teaching aids of higher educational institutions.